Sequencing of metals in multivariate metal-organic frameworks - Ji, Zhe; Li, Tong; Yaghi, Omar M. (Science (American Association for the Advancement of Science), 2020)
Most metal-organic frameworks (MOFs) contain just one type of metal in the nodes connecting the organic linkers. Multivariate MOFs containing multiple metals can offer greater selectivity in sorption and catalytic properties, but determining the arrangement of metals in these materials is challenging. Ji et al. found that atom-probe tomography can reveal sequences of metals for MOF-74 single crystals containing combinations of cobalt, cadmium, lead, and manganese ions. In this MOF, the metals form oxide rods that are connected by the organic linker into a honeycomb lattice. The obtained sequences, which were tuned by varying the proportion of metals and synthesis temperature, could be random, short and long duplicates, and single metal insertions. Science , this issue p. 674 Atom-probe tomography revealed the metal sequences in the oxide rods in a multivariate metal-organic framework compound. We mapped the metal sequences within crystals of metal-oxide rods in multivariate metal-organic framework–74 containing mixed combinations of cobalt (Co), cadmium (Cd), lead (Pb), and manganese (Mn). Atom probe tomography of these crystals revealed the presence of heterogeneous spatial sequences of metal ions that we describe, depending on the metal and synthesis temperature used, as random (Co, Cd, 120°C), short duplicates (Co, Cd, 85°C), long duplicates (Co, Pb, 85°C), and insertions (Co, Mn, 85°C). Three crystals were examined for each sequence type, and the molar fraction of Co among all 12 samples was observed to vary from 0.4 to 0.9, without changing the sequence type. Compared with metal oxides, metal-organic frameworks have high tolerance for coexistence of different metal sizes in their rods and therefore assume various metal sequences.